The prisoner in the castle : a Maggie Hope mystery - MacNeal, Susan Elia (MacNeal, Susan Elia. Maggie Hope mystery, 2018)
"American-born spy and code-breaker extraordinaire Maggie Hope must solve a baffling series of murders among a group of captive agents on an isolated Scottish island as the acclaimed World War II mystery series from New York Times bestselling author Susan Elia MacNeal continues. Maggie Hope is being held prisoner on a remote Scottish island with other SOE agents who know too much for the enemy's comfort. All the spies on the island are trained to kill--and when they start dropping off one-by-one, Maggie needs to find the murderer... before she becomes the next victim"--